2012
DOI: 10.1097/olq.0b013e318273718e
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of Sexually Transmitted Infections and Care-Seeking Behaviors of Male Clients of Female Sex Workers in Bangladesh

Abstract: Reported risk behaviors, STI symptoms and care-seeking behavior suggest that MCs are a potential risk group for transmission of HIV and STIs. The study findings underscore the need to target HIV/STI prevention intervention for MCs, which are predominantly geared toward FSWs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The majority of FSWs in our study sought care from DIC, which is similar to a study in Laos where 53% of FSWs reported receiving care from DIC [40]. While care seeking for STIs by male partners of FSWs in Bangladesh was dominated by pharmacies[41], only 16% of FSWs reported seeking care from pharmacies. DICs appear to be successful in providing STI services to FSWs and should be considered as a important program to improve SRH among this population.…”
Section: Discussionsupporting
confidence: 82%
“…The majority of FSWs in our study sought care from DIC, which is similar to a study in Laos where 53% of FSWs reported receiving care from DIC [40]. While care seeking for STIs by male partners of FSWs in Bangladesh was dominated by pharmacies[41], only 16% of FSWs reported seeking care from pharmacies. DICs appear to be successful in providing STI services to FSWs and should be considered as a important program to improve SRH among this population.…”
Section: Discussionsupporting
confidence: 82%
“…The study findings suggest that a range of formal and informal healthcare providers provide SRH services to married men in the three study areas. Informal healthcare providers are those who do not have a formal medical degree but provide treatment mostly in the rural areas and urban slums in Bangladesh [ 17 ]. These providers range from village doctors (sometimes called rural medical practitioners or palli chikitsok ) to faith healers ( hujur, pir and fakir ), drug store salespeople, street-based medicine sellers, kabiraj and hakim (herbalists).…”
Section: Resultsmentioning
confidence: 99%
“…Given this shortage of formal providers and mushrooming of informal providers, it is quite realistic that many men will solve their SRH concerns by consulting with the informal providers. A study conducted by Ahmed et al on care-seeking behaviors for STDs among male clients of female sex workers in Bangladesh found that 52.3% of the participants had received treatment from drug store salespeople and local healers, whereas only 37.4% received treatment from qualified medical professionals [ 17 ]. Similar reports of men underutilizing formal health care services due to limited financial resources were found in other studies [ 14 – 16 , 18 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Directorate of Drug Administration, there are approximately 70,000 registered drug retailers in Bangladesh and an additional 30,000 without licenses [ 15 ]. A study conducted among informal health providers in rural Bangladesh reported that only half of the MSs working in drug stores had any kind of training, leaving the other half without any kind of training whatsoever [ 16 , 17 ]. Previous studies in Bangladesh and other developing countries reported that MSs had difficulties in recognizing STI symptoms, offered medications not recommended, seldom referred clients to qualified physicians, and were less likely to counsel patients for condom use or partner treatment [ 5 , 7 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%